2021
DOI: 10.3390/tourhosp2010006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Having a Holiday or Work in Fiji on Perceived Immune Fitness

Abstract: The Western 24 h society poses great psychological and physical demands on people, which may result in complaints such as stress or being overworked, and reduced immune fitness. Having a holiday may be a good way to reduce work-related stress and reduced mood and improve perceived immune fitness. Therefore, the aim of the current study was to assess the impact of having a holiday or work on perceived immune fitness and mood. A survey was held among N = 246 young adults who were on holiday in Fiji, and N = 87 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…The study’s most intriguing findings concern the immune health status of our participants with a borderline ISQ score. Consistently, borderline ISQ score of 6.2 was also reported among young students from Verster et al (2021) . Females currently have significantly lower ISQ scores than males, suggesting a better immunological status among males than female, which agrees with previous research from the Netherlands, though a different tool was used (IFQ) ( Lantman et al, 2017 ).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The study’s most intriguing findings concern the immune health status of our participants with a borderline ISQ score. Consistently, borderline ISQ score of 6.2 was also reported among young students from Verster et al (2021) . Females currently have significantly lower ISQ scores than males, suggesting a better immunological status among males than female, which agrees with previous research from the Netherlands, though a different tool was used (IFQ) ( Lantman et al, 2017 ).…”
Section: Discussionsupporting
confidence: 68%
“…Females currently have significantly lower ISQ scores than males, suggesting a better immunological status among males than female, which agrees with previous research from the Netherlands, though a different tool was used (IFQ) ( Lantman et al, 2017 ). Females have reported poorer sleep ( Ibrahim et al, 2017 ; Burgard & Ailshire, 2013 ), more consumption of fast food ( Yardimci et al, 2012 ), and to be more likely to have a sedentary lifestyle ( Varela-Mato et al, 2012 ; Edwards & Sackett, 2016 ) anxiety and stress ( Verster et al, 2021 ) compared to males, which may explain the observed sex disparities due to the association of these conditions with various aspects of immune system as discussed earlier. This is also apparent in the present study, which found that females reported less physical activity and sleep duration than males.…”
Section: Discussionmentioning
confidence: 97%
“…The use of 1-item scales has been validated previously [33], and these mood ratings have been applied successfully in previous studies [36][37][38]. Additionally, the 1-item assessment of 'being active' has been successfully applied in previous research [39,40]. The items were rated for (1) the year 2019 (the period before COVID-19), (2) the first lockdown period (15 March-11 May 2020), (3) summer 2020 (no lockdown) and ( 4) the second lockdown (November 2020-April 2021).…”
Section: Mood and Being Activementioning
confidence: 99%
“…For the present analysis, data on sex, height, age, and perceived immune fitness from various studies were pooled [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Studies were included if immune fitness was assessed with the immune status questionnaire (ISQ) and/or single item perceived immune fitness scale.…”
Section: Methodsmentioning
confidence: 99%